Conocimientos y mitos sobre menopausia en mujeres de edad fértil del barrio Zhucos de la ciudad de Loja, agosto 2014-abril 2015 - Torres Jumbo, María Elena (2016)
Menopause is a more complex than the end of menstruation process is a concept built from the biological, social and especially from the cultural context involving a wide range of behaviors and expressions of one woman to another. It is a process that occurs around fifty years of life, a situation that requires a holistic view of this phenomenon, through the study of the life cycle, physiology and cultural fabric and thus the particular conditions of life and feelings against This process. This research is a type design Descriptive and quantitative approach; It was raised as main objective to characterize the knowledge and myths about menopause with women of childbearing age Zhucos neighborhood. Based on this, a questionnaire to 73 women whose results show that most women investigated level of primary and secondary education know what menopause is applied. Regarding evidenced myths that still exist in a large group of women Zhucos, myths that are rooted in their idiosyncrasies, childrearing and cultural influence family and community. KEYWORDS: Knowledge, Myth, Menopause